Cruciate Ligament Cell Sheets Can Be Rapidly Produced on Thermoresponsive poly(glycidyl ether) Coating and Successfully Used for Colonization of Embroidered Scaffolds - Zahn, Ingrid; Stoebener, Daniel David; Weinhart, Marie; Goegele, Clemens; Breier, Annette; Hahn, Judith; Schroepfer, Michaela; Meyer, Michael; Schulze-Tanzil, Gundula (Cells, 2021)
Anterior cruciate ligament (ACL) cell sheets combined with biomechanically competent scaffolds might facilitate ACL tissue engineering. Since thermoresponsive polymers allow a rapid enzyme-free detachment of cell sheets, we evaluated the applicability of a thermoresponsive poly(glycidyl ether) (PGE) coating for cruciate ligamentocyte sheet formation and its influence on ligamentocyte phenotype during sheet-mediated colonization of embroidered scaffolds. Ligamentocytes were seeded on surfaces either coated with PGE or without coating. Detached ligamentocyte sheets were cultured separately or wrapped around an embroidered scaffold made of polylactide acid (PLA) and poly(lactic-co-epsilon-caprolactone) (P(LA-CL)) threads functionalized by gas-phase fluorination and with collagen foam. Ligamentocyte viability, protein and gene expression were determined in sheets detached from surfaces with or without PGE coating, scaffolds seeded with sheets from PGE-coated plates and the respective monolayers. Stable and vital ligamentocyte sheets could be produced within 24 h with both surfaces, but more rapidly with PGE coating. PGE did not affect ligamentocyte phenotype. Scaffolds could be colonized with sheets associated with high cell survival, stable gene expression of ligament-related type I collagen, decorin, tenascin C and Mohawk after 14 d and extracellular matrix (ECM) deposition. PGE coating facilitates ligamentocyte sheet formation, and sheets colonizing the scaffolds displayed a ligament-related phenotype.
CRIS-Team WoS Importer:2021-05-14